The combined impact of metabolic gene polymorphisms on elite endurance athlete status and related phenotypes - Ahmetov, I. I.; Williams, A. G.; Popov, D. V.; Lyubaeva, E. V.; Hakimullina, A. M. (Human Genetics, 2009)
Endurance performance is a complex phenotype subject to the inXuence of both environmental and genetic factors. Although the last decade has seen a variety of speciWc genetic factors proposed, many in metabolic pathways, each is likely to make a limited contribution to an 'elite' phenotype: it seems more likely that such status depends on the simultaneous presence of multiple such variants. The aim of the study was to investigate individually and in combination the association of common metabolic gene polymorphisms with endurance athlete status, the proportion of slow-twitch muscle Wbers and maximal oxygen consumption. A total of 1,423 Russian athletes and 1,132 controls were genotyped for 15 gene polymorphisms, of which most were previously reported to be associated with athlete status or related intermediate phenotypes. Muscle Wber composition of m. vastus lateralis in 45 healthy men was determined by immunohistochemistry. Maximal oxygen consumption of 50 male rowers of national competitive standard was determined during an incremental test to exhaustion on a rowing ergometer. Ten 'endurance alleles' (NFATC4 Gly160, PPARA rs4253778 G, PPARD rs2016520 C, PPARGC1A Gly482, PPARGC1B 203Pro, PPP3R1 promoter 5I, TFAM 12Thr, UCP2 55Val, UCP3 rs1800849 T and VEGFA rs2010963 C) were Wrst identiWed showing discrete associations with elite endurance athlete status. Next, to assess the combined impact of all 10 gene polymorphisms, all athletes were classiWed according to the number of 'endurance' alleles they possessed. The proportion of subjects with a high (¸9) number of 'endurance' alleles was greater in the best endurance athletes compared with controls (85.7 vs. 37.8%, P = 7.6 £ 10¡6). The number of 'endurance' alleles was shown to be positively correlated (r = 0.50; P = 4.0 £ 10¡4) with the proportion of fatigue-resistant slow-twitch Wbers, and with maximal oxygen consumption (r = 0.46; P = 7.0 £ 10¡4). These data suggest that the likelihood of becoming an elite endurance athlete depends on the carriage of a high number of endurance- related alleles.